Assessment of inorganic and nutrient contamination levels for improvement of water quality in Estero de San Miguel using granulated coal ash - Lee, Bea Krisha C.
In Estero de San Miguel, large amounts of untreated wastewater are directly discharged into the water body. Water quality deteriorates due to decomposition of organic matter resulting into several environmental problems such as hypoxia, eutrophication, and bad odor. It has been reported that granulated coal ash (GCA) can be used as an absorbent material. It has been widely used in Japan for improving sediment and water quality in littoral regions. The aim of this study is to examine the efficiency of GCA in improving water quality in Estero de San Miguel. This study aims to apply GCA in wastewater with different characteristics from that in Japan. Wastewater collected from Estero de San Miguel was poured into containers filled with different volumes of GCA. Samples were taken from each container at different retention times (7, 14, and 22 days), and measured for water quality parameters (e.g., pH, redox potential, nutrient salts). Dissolution of chemical components of GCA was confirmed with the increase in sulfate concentration, pH, and electrical conductivity measured in the sample, and the amount of dissolution from GCA was found to be proportional to the volume of GCA. The decrease in phosphate concentration was observed to be proportional with the volume of GCA, indicating the removal of phosphate also by eluted ions from GCA. The ammonia concentration and odor level in the cases with GCA were found to be relatively lower than those in the control case, suggesting the adsorption of ammonia and odor by GCA. It can be concluded from our results that GCA can be used to improve water quality in Estero de San Miguel.